Customer centricity: a bibliometric analysis of academic production - Damázio, Luciana Faluba; Soares, João Luiz; Shigaki, Helena Belintani; Gonçalves, Carlos Alberto; Mesquita, José Marcos Carvalho de (Revista de Administração da UFSM, 2020)
Purpose – This article presents a bibliometric analysis of the literature with the purpose of contributing to a better understanding of the evolution of the theme, and the clarification of concepts and terms associated with the Customer Centricity area. Design/ Methodology/ Approach – In this study, 656 articles indexed by Scopus in the last 26 years were analyzed with the software VOSViewer. Findings – It can be concluded that the theme is still incipient in terms of scientific production, given the volume of articles identified in this study compared to other more robust themes in the marketing area, but which has been growing and attracting the interest of researchers over the past few years. Originality/ Value – It was possible to verify that Customer Centricity represents a phenomenon that has been studied recently with considerable intensity, notably since 2007.